Allergic Myocardial Infarction: A Clinical Perspective on Kounis Syndrome - Thapa, Ajay Singh; Shrestha , Aishworya (Journal of National Heart and Lung Society Nepal, 2024)
Kounis syndrome is defined as an acute coronary syndrome occurring in the setting of a hypersensitivity, allergenic, anaphylactic, or anaphylactoid reaction. The syndrome involves mast cell activation and the release of inflammatory mediators, leading to coronary vasospasm, plaque rupture, or thrombosis during allergic or anaphylactic reactions. It is an underdiagnosed life-threatening medical emergency. As a wide array of drugs, foods, environmental conditions such as Hymenoptera sting, and disease states may be associated with Kounis Syndrome, it is essential for clinicians to maintain a thorough understanding of its pathophysiology, clinical presentation, and associated risks. This article reviews the pathophysiology, classification, clinical presentation, diagnostic approach, and management strategies of Kounis syndrome, with reference to recent guidelines and case studies.